The prevalence of dental caries among Schoolchildren in a sample of schools in Ajdabiya City; A cross-sectional study - M. Mukhtar, Hala; A. Almajbrey, Asmaa; A. Al-bardah, Salmeen; F. Alhendawy, Faraj (Benghazi University Medical Journal, 2025)
Background: Dental caries is an infectious microbiological disease of the teeth that results in localized dissolution and destruction of the calcified dental tissues. It remains one of the most prevalent pathological conditions among children in most countries. Preventive measures are the cornerstone of successful treatment for dental caries in children. Aims: The aim of this study is to determine the prevalence of caries among schoolchildren in the city of Ajdabiya and to lay the foundation for future awareness and educational programs on oral and dental health. These initiatives aim to prevent early tooth loss resulting from dental caries. Methods: This observational cross-sectional study was conducted among 690 schoolchildren (both female and male) in six randomly selected government schools in Ajdabiya city, located in northeastern Libya. A clinical examination was performed on the children. If caries were detected, a mark was placed next to the symbol representing the affected tooth on a designated recording sheet, according to the age groups targeted in the study. Data were analyzed using SPSS version 25. Results: The prevalence of dental caries among the study population was high, at 84%, with the highest rates observed among 9- and 10-year-old children—95% and 94%, respectively. Conclusions: Dental caries is considered a highly prevalent public health problem among children worldwide. This study highlights a high prevalence of dental caries among schoolchildren in Ajdabiya city, correlating with the mixed dentition stage—a phase in which permanent teeth have erupted while primary teeth are still present.